The effect of workload and work environment on teacher turnover intention with compensation as a moderating variable at Sinar Cendekia School, South Tangerang - Ahmad Marzuki; Tajuddin Pogo (Dinasti International Journal of Education Management And Social Science, 2023)
This study aims to analyze and explain the effect of workload and work environment on teacher turnover intention with compensation as a moderation variable. The population of this study was all permanent teachers at Sinar Cendekia School, South Tangerang, with a total of 102 respondents. A quantitative type of research, the sampling method is a saturated sample method, that is, all populations become research samples. Data collection techniques from the results of interviews and dissemination of questionnaires to 102 respondents. Data analysis using Structural Equation Model – Partial Least Square (SEM – PLS). The results found that compensation has a positive and significant effect on teacher turnover intention. Workload has a positive and significant effect on teacher turnover intention. The work environment has a positive, but insignificant effect on teacher turnover intention. Compensation has a positive and significant effect on workload with the salary dimension having the strongest effect. Compensation has a positive and significant effect on the work environment, with the facility dimension having the strongest effect. Compensation moderates workload and has a positive and significant effect on teacher turnover intention. Compensation moderates the work environment and has a positive but insignificant effect on teacher turnover intention at Sinar Cendekia School.